Potential public health impact of the adjuvanted recombinant zoster vaccine among people aged 50 years and older in Beijing - Christa Lee; Ning Jiang; Haiwen Tang; Chiyu Ye; Yanfei Yuan; Desmond Curran (Taylor & Francis Group, 2021)
Herpes zoster (HZ) is a painful, unilateral rash which occurs upon reactivation of latent varicella zoster virus due to age-related immunity decline or immuno-suppression. In 2019, the recombinant zoster vaccine (RZV) was the first vaccine to be approved in China for HZ prevention. This study aimed to estimate the potential public health impact of RZV vaccination, compared with the status quo of no vaccination, in individuals ≥50 years of age (YOA) in Beijing, by adapting the published ZOster ecoNomic Analysis (ZONA) model. We considered 5% and 50% vaccination coverage for the private market (near-term post-launch) and mass vaccination (long-term) settings respectively. In the base-case analysis of both market settings, second-dose compliance was set to 80%. Coverage and second-dose compliance rates were varied under scenario and sensitivity analyses. In the base case, mass vaccination with RZV was estimated to prevent 435,681 HZ cases, 51,558 postherpetic neuralgia (PHN) cases, and 15,703 cases of other HZ-related complications in the overall ≥50 YOA cohort over their remaining lifetime, compared with no vaccination. Under the same base-case scenario, 14,247 hospitalizations and 1,031,387 outpatient visits could be avoided. The 50-59 YOA cohort had the highest contributions to the overall reduction in HZ cases, its complications and related healthcare resource utilization. Results were robust under numerous scenario and sensitivity analyses. This analysis demonstrates the potential of RZV vaccination to substantially reduce the public health burden of HZ among individuals ≥50 YOA, and may inform appropriate vaccination strategies for HZ prevention, particularly in urban settings within China.